Nichiren Shoshu Buddhism - Causton, Richard (Harper & Row, 1989)
Mr. Richard Causton, or "Dickie" to those of us who knew and loved him, was the honorable General Director of Soka Gakkai International-United Kingdom (SGI-UK) until his death in 1995 at the age of 75. A couple of years before his passing, Mr. Causton initiated the revision of this book with the assistance of his good friend and professional writer Eddy Canfor-Dumas. In what would become one of the final major accomplishments of his life's mission, in 1994 Mr. Causton finalized the revised text and renamed this book "The Buddha in Daily Life - An Introduction to the Buddhism of Nichiren Daishonin."